HUBUNGAN KECEPATAN DAN KELINCAHAN TERHADAP KEMAMPUAN MENGGIRING BOLA PADA SISWA EKTRAKURIKULER SEPAKBOLA SMP NEGERI 7 MIMIKA - Yohanes B D Horokubun (SATRIA : Journal of Sports Athleticism in Teaching and Recreation on Interdisciplinary Analysis, 2022)
Football is a very popular sport in the world, when compared to other popular sports, football is far superior to having a lot of fans spread all over the world. Basic techniques in the game of football are basic movements that must be mastered by every football player. The purpose of this study was to determine the relationship between speed and agility on the ability to dribble in soccer extracurricular students at SMP Negeri 7 Mimika. This type of research is quantitative research. Methods of data collection by using a questionnaire. The location of this research is SMP 7 Mimika with a sample of 21 students. Data analysis using normality test, linearity test and hypothesis testing. Research results There is a significant relationship between speed and dribbling ability of students. With r count of 0.613, it is greater than r table at = 5% with N = 21 of 0.352. In the agility variable, the correlation coefficient r arithmetic (0.595) > (0.352) r table at a significance level of 5%. Based on the results of the analysis above, the correlation coefficient between speed and agility on the ability to dribble is 0.653, which is positive. The magnitude of the relationship between speed and agility with the ability to dribble is known by the value of r (R2 x 100%). The value of R2 is 0.427, so the magnitude of the relationship is 42.7%, while the remaining 57.3% is influenced by other factors not examined in this study.